Methylphenidate and Morphine Combination Therapy in a Rat Model of Chronic Pain. (February 2020) - You, Zerong; Ding, Weihua; Doheny, Jason T.; Shen, Shiqian; Yang, Jinsheng; Yang, Liuyue; Chen, Lucy; Zhu, Shengmei; Mao, Jianren
Abstract : BACKGROUND: The incremental dose of opioids used in chronic pain management often leads to a reduced opioid analgesic effect, opioid misuse, and addiction. Central dopamine (DA) dysfunction contributes to the chronicity of pain and a decreased opioid analgesic effect. Methylphenidate (MPH/Ritalin) enhances central DA function by inhibiting DA reuptake. In this study, we used a rat model of chronic pain to examine whether combination of MPH with morphine (MOR) would improve the MOR analgesic effect under a chronic pain condition. METHODS: Tibiotarsal joint Complete Freund's Adjuvant (CFA) injection in rats was utilized to induce chronic nociception. The analgesic effect of low-dose MPH (0.25 mg/kg), low-dose MOR (2.5 mg/kg), and their combination was examined in CFA rats. Nociceptive behavior was assessed by von Frey test. Conditioned place preference (CPP) and open field tests (OFTs) were used to examine the rewarding behavior and locomotor activity in rats, respectively. RESULTS: Our findings are as follows: (1) in CFA rats with chronic pain, 2.5 mg/kg of MOR had less analgesic effect than 10 mg/kg of MOR at 28 days after injury (95% confidence intervals [CIs] for difference of means of von Frey threshold in gram: −11.9 [−6.5 to −17.3]); (2) in the 1-hour time window of 30–90 minutes after injection, the combination of MPH (0.25 mg/kg) with MOR (2.5 mg/kg) increased synergistically and prolonged the analgesic effect in CFA rats as compared with MPH or MOR alone ( P = .01 for MPH by MOR interaction, and 95% CIs for difference of means of von Frey threshold in gram: 3.3 [1.37–6.12] for the combination versus MPH and 3.2 [1.35–5.74] for the combination versus MOR); (3) at the low dose (0.25 mg/kg), MPH did not increase locomotor activity (MOR + MPH versus MOR, P = .13) nor significantly enhanced MOR reward behavior (MOR + MPH versus MOR, P = .63) in CFA rats. CONCLUSIONS: Our data suggest that a combination therapy using low-dose MPH and MOR may produce a MOR-sparing effect in chronic pain management.